José Antonio Lutzenberg: trajetória de vida, obra e contribuição para a causa ambiental no Brasil - Augusto, Janaina da Silva (2010)
The aim of this work is to compare adversative constructions and concessive constructions which occur in editorials. This paper is based on the theory of functional grammar, which postulates the conjunction of syntactic, semantic and pragmatic factors in the analysis of linguistic use. Taking these aspects into consideration, it intends to investigate possible reasons which motivate the use of one construction instead of the other in particular contexts. The results reached show that, on one hand, there are areas of overlap between adversative constructions and concessive constructions for the fact that they display relation of preference (GARCÍA, 1994). On the other hand, there are areas of contrast between these constructions due to the fact that each of them plays a particular role in certain contexts, which is resulted from the specific functions fulfilled by a concessive element, as margin (LONGACRE, 2007), satellite (DIK, 1989; MATTHIESSEN & THOMPSON, 1988), enhancement (HALLIDAY, 2004), guidepost (CHAFE, 1984, apud DECAT, 1993), background (GIVÓN, 1990) and theme (GARCÍA, 1994). In the analysis, it was observed that most of the differences between the constructions in discussion are related to the fact that specifically the concessive element, as margin or satellite, can present mechanism of anticipation, displaying particular effects